When the Power is Out: Strategizing for Electricity Disruptions in Lilongwe - Jana, Wilfred (Department of Environmental and Geographical Science, 2022)
Electricity disruptions are a common feature of cities of the global south. However, not much is known of how households cope, and strategize around these electricity disruptions. In this thesis, I focus on middle-class households in Lilongwe, who are connected to the formal electricity grid but experience frequent power cuts. I examine this space of disrupted electricity, paying attention to household's experiences. I explore the varied ways in which households cope with and navigate around disruptions, by piecing together an array of technologies and infrastructures. Drawing on in-depth interviews and observation, I argue that households build assemblages of infrastructures, bringing into their energy sources a mix of older technologies, as well as new ones, to ensure an uninterrupted flow of energy even during an electricity disruption. Households find alternative ways to link to power, by reorganising themselves, their energy choices and food choices. In this piecing together, households themselves constitute a critical infrastructure that makes the alternative technologies work. It takes their agency, knowledge, and creativity to piece the multiple technologies together, bridge them, and make them work. In short, I demonstrate that in the event of a power disruption, households do not sit back and wait passively for electricity to come back on. They plan and strategize, making do using any resources within their capacities. A form of infrastructural citizenship, making do around electricity disruptions has the potential to reconfigure citizenship.